PENGARUH MENONTON ANIMASI JEPANG DI INTERNET TERHADAP GAYA HIDUP WIBU DI YOGYAKARTA - Pristianti, Khoirunissa (Commsphere: Jurnal Ilmu Komunikasi, 2024)
Popular culture refers to those cultural elements that are best known, accepted, and consumed by the majority of society. It covers various aspects of daily life, such as music, films, television, fashion, food and other trends. Like this research, it focuses on three main operational indicators of anime consumption: preference, frequency, and attention. The sample consisted of 50 participants randomly selected from the wibu population during the Jejepangan cosplay event in Yogyakarta, with the aim of identifying and analyzing the influence of Japanese animation (anime) on the lifestyle behavior of wibu fans in Yogyakarta, especially in terms of consumption patterns, clothing choices, and merchandise purchases . This research uses a Likert scale questionnaire designed to measure the extent to which anime influences changes in consumption patterns, clothing choices and merchandise purchases. The results of the research, the results of statistical analysis in the F test, obtained an F value of 55.527 with a probability value (sig) = 0.000. It is known that Ftable with a total of 50 respondents is 4.04, so that the Fcount value > Ftable (55.527)> Ftable (4.04), and the sig value is smaller than the probability value of 0.05 or the value of 0.000<0.05. So it can be concluded that, variable x, namely the influence of watching Japanese animation on the internet (simultaneously), has a significant effect on variable y, namely the lifestyle of wibu in Yogyakarta. The conclusions of this study provide valuable insight into the influence of Japanese anime on the lifestyle of weibu individuals in Yogyakarta. These findings confirm the researchers' hypothesis that watching anime over the internet significantly influences weeaboo lifestyle choices, including clothing preferences, participation in events, and consumption patterns. Keywords: Japanesse Animation, Fans, Internet, Lifestyle